2013
DOI: 10.5296/ijhrs.v3i2.4135
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Students Motivation to Learn in Bahauddin Zakariya University, Multan (Pakistan)

Abstract: Abstract:Motivation is the paramount medium and obligatory precondition that provoke critical thinking among the students. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 22 publications
3
14
0
4
Order By: Relevance
“…Nurse educators' reasons for applying motivational strategies in their teaching/learning process are divers and include: to support learning and future goals, establish relevance and connecting to students' interest, treat students as uniquely valued individuals and foster student valuing and perception with grand mean 3.45, SD±0.62. This is in line with the findings of [16], where usage of effectual teaching methodologies, adequate learning environment in the classroom, self-motivated involvement of the students, large class size etc were the foremost determinants that can increase the students motivation for learning process.…”
Section: Nurse Educators' Reasons For Applying Motivational Strategies In Teaching-learning Processsupporting
confidence: 90%
“…Nurse educators' reasons for applying motivational strategies in their teaching/learning process are divers and include: to support learning and future goals, establish relevance and connecting to students' interest, treat students as uniquely valued individuals and foster student valuing and perception with grand mean 3.45, SD±0.62. This is in line with the findings of [16], where usage of effectual teaching methodologies, adequate learning environment in the classroom, self-motivated involvement of the students, large class size etc were the foremost determinants that can increase the students motivation for learning process.…”
Section: Nurse Educators' Reasons For Applying Motivational Strategies In Teaching-learning Processsupporting
confidence: 90%
“…Motivation is defined as the desire of a person to perform activities. Lack of motivation causes pessimism, anxiety, and failure in learning (6,7). Students, as a vulnerable group, may experience changes in motivation for learning due to various reasons such as separation from family and experiencing new social communications (5,8).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the important role of motivation for learning among public health students, studies have shown that this group of students does not possess sufficient motivation for learning and education, and further, that they experience depression more often than students of other health sciences and medical majors (1,11). Several domestic and international studies have attributed students' motivation for learning to factors such as providing feedback, students' encouragement, educational methods, teacher's behavior (6), major, environmental factors, and educational facilities of universities (12,13). However, these studies have been carried out using a quantitative approach and have not investigated the students' perspectives, especially public health students, about the components of motivation for learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Student learning model can be accessed through the pattern of teaching done by an educator (Ullah et al, 2013). From research conducted by Qurnain & Peni (2013), the use of Quantum Teaching (QT) is known superior to other learning, this is because through QT, educators can create a cool and fun learning atmosphere in the classroom.…”
Section: Score Motivation Indicatorsmentioning
confidence: 99%